2013
DOI: 10.1002/etc.2094
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of atmospherically deposited organic contaminants at high elevation in yosemite national park, California, USA

Abstract: Abstract-Contaminants used at low elevation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Other studies of pesticide distribution have supported the negative correlation between elevation and pesticide concentrations (Mast et al, 2012). There are exceptions that have been found such as McGee Lake in the McGee Creek drainage (Bradford et al, 2013). Although this lake is still considered high elevation (2470 m), other topographical factors should be taken into consideration to understand why this lake is notably different.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies of pesticide distribution have supported the negative correlation between elevation and pesticide concentrations (Mast et al, 2012). There are exceptions that have been found such as McGee Lake in the McGee Creek drainage (Bradford et al, 2013). Although this lake is still considered high elevation (2470 m), other topographical factors should be taken into consideration to understand why this lake is notably different.…”
Section: Discussionmentioning
confidence: 94%
“…There is also loss of mass of CPY by transport from air to the ground, specifically due to deposition in rain or snow, sorption to aerosol particles that subsequently are deposited by wet and dry deposition, and direct sorption to terrestrial and aquatic surfaces as shown by Aston and Seiber (1997), LeNoir et al (1999) and Bradford et al (2013). Estimates of these process rates can be made and the overall results can be compared to measured concentrations of CPY.…”
Section: Model Of Long Range Transport and Characteristic Travel Distmentioning
confidence: 99%
“…Airborne contaminants (including pesticides) originating in California's agricultural Central Valley are transported downwind to the Sierra Nevada (24,25) and may also have impacts on amphibians (26,27). However, an explicit link between pesticides and R. sierrae declines is lacking.…”
mentioning
confidence: 99%